Integrin Activation Enables Sensitive Detection of Functional CD4+ and CD8+ T Cells: Application to Characterize SARS-CoV-2 Immunity - Schöllhorn, Anna; Schuhmacher, Juliane; Besedovsky, Luciana; Fendel, Rolf; Jensen, Anja T. R.; Stevanović, Stefan; Lange, Tanja; Rammensee, Hans-Georg; Born, Jan; Gouttefangeas, Cécile; Dimitrov, Stoyan (Frontiers in Immunology, 2021)
We have previously shown that conformational change in the β2-integrin is a very early activation marker that can be detected with fluorescent multimers of its ligand intercellular adhesion molecule (ICAM)-1 for rapid assessment of antigen-specific CD8+ T cells. In this study, we describe a modified protocol of this assay for sensitive detection of functional antigen-specific CD4+ T cells using a monoclonal antibody (clone m24 Ab) specific for the open, high-affinity conformation of the β2-integrin. The kinetics of β2-integrin activation was different on CD4+ and CD8+ T cells (several hours vs. few minutes, respectively); however, m24 Ab readily stained both cell types 4–6 h after antigen stimulation. With this protocol, we were able to monitor ex vivo effector and memory CD4+ and CD8+ T cells specific for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), cytomegalovirus (CMV), Epstein–Barr virus (EBV), and hepatitis B virus (HBV) in whole blood or cryopreserved peripheral blood mononuclear cells (PBMCs) of infected or vaccinated individuals. By costaining β2-integrin with m24 and CD154 Abs, we assessed extremely low frequencies of polyfunctional CD4+ T cell responses. The novel assay used in this study allows very sensitive and simultaneous screening of both CD4+ and CD8+ T cell reactivities, with versatile applicability in clinical and vaccination studies.